Raman shift and electrical properties of MoS2 bilayer on boron nitride substrate. (2nd July 2015) - Li, Lijun; Lee, Inyeal; Lim, Dongsuk; Kang, Moonshik; Kim, Gil-Ho; Aoki, Nobuyuki; Ochiai, Yuichi; Watanabe, Kenji; Taniguchi, Takashi
Abstract: We have fabricated a bilayer molybdenum disulphide (MoS2 ) transistor on boron nitride (BN) substrate and performed Raman spectroscopy and electrical measurements with this device. The characteristic Raman peaks show an upshift about 2.5 cm −1 with the layer lying on BN, and a narrower line width in comparison with those on a SiO2 substrate. The device has a maximum drain current larger than 1 μ A and a high current on/off ratio of greater than 10 8 . In the temperature range of 100 K−293 K, the two terminal gate effect mobility and the carrier density do not change significantly with temperature. Results of the Raman and electrical measurements reveal that BN is a suitable substrate for atomic layer electrical devices.